Prospects, Risks, and Vulnerabilities in Emerging and Developing Economies : Lessons from the Past Decade - Ruch, Franz Ulrich (World Bank, Washington, DC, 2020)
Growth in emerging markets and developing economies (EMDEs) has generally disappointed since the 2009 global recession, with sizable forecast downgrades in most years. EMDEs continue to face downside risks to growth outlook over the next couple of years. These include heightened global policy uncertainty, trade tensions, spillovers from weaker-than-expected growth in major economies, and disorderly financial market developments. These risks are accompanied by region-specific risks, including geopolitical tensions, armed conflict, and severe weather events. If risks materialize, their impact on EMDEs depends on the magnitude of spillovers and domestic vulnerabilities. Since the 2009 global recession, external, corporate sector and sovereign vulnerabilities have risen in most EMDEs, leaving them less well-prepared for future shocks. Low-income countries, in particular, face elevated vulnerabilities, with about 40 percent of them currently in debt distress. Over the longer run, EMDEs also face weakening potential growth, reflecting decelerations in capital accumulation and productivity growth, as well as demographic headwinds. These constraints are likely to hamper growth in the next decade unless they are mitigated by ambitious and credible reform agendas.